"Neither Catholic Fish nor Protestant Fowl" the question of Anglicanism - Inman, Daniel D. 1984- (2018)
Any claim for the ecclesiological integrity of Anglicanism seems, at the moment, tenuous. The divisions within the Anglican Communion over the issues of human sexuality and gender do not seem easily healed, despite the efforts of the current archbishop of Canterbury, Justin Welby, and his predecessor, Rowan Williams. Despite the proud assertions of Anglican apologists down the ages that the Church was positioned, following the Elizabethan "settlement" of 1588, with moderation and good sense as a via media between Rome and Geneva, this new five-volume history of Anglicanism reveals a church that has been in conflict from its very origins. In seeking to be a church for the whole of England, it was naturally constituted of competing theological and ecclesiological visions, influenced by continental reformations, that could never be entirely congruent - divisions which, at certain junctions since the break with Rome almost 500 years ago, have been the source of significant aggravation and tribalism. Those politico-theological tensions, the History underlines, were exported across Britain's expanding empire, spawning vibrant new networks and associations that only served further to disrupt the fragile unity of the Church of England after the confessional state was dismantled by the British parliament in 1828-1832. Despite the enormous vibrancy engendered by this conflict of traditions, now stretched across a global Communion and influenced as much by post-colonialism and globalisation as older theological traditions, the final two volumes pose challenging questions for any who would seek to speak meaningfully of a single entity called the "Anglican Church". This article suggests that the greatest threat to contemporary Anglicanism, however, lies in a postmodern retreat from the ecumenical task as truth becomes ever more contextualised, driven by a desire for peaceful cohabitation rather than institutional coherence. These volumes might suggest, rather, that Anglicanism's hope (and its gift to the wider Church) is to be found precisely in its conflicted quest for truth and unity in faithful response to Scripture, tradition and reason.
Keywords: Anglicanism; British Empire; Church of England; Ecclesiology; Ecumenism; Postcolonialism; Reformation